Contributions to the wild bee fauna in Argentina (Hymenoptera: Anthophila) - Alvarez, Leopoldo Jesús (2024)
Argentina is the country with the second highest number of bee species in the Neotropics after Brazil. Fifteen new records of wild bees belonging to genera of the families Apidae, Andrenidae, Colletidae, Halictidae, and Megachilidae are presented. Species of genera Callonychium Brèthes (Andrenidae), Gaesischia Michener, LaBerge & Moure, Melitoma Lepeletier & Serville, Trichocerapis Cockerell (Apidae), Hylaeus Fabricius (Colletidae), Habralictus Moure, Megalopta Smith, NeocorynuraSchrottky, Pseudaugochlora Michener, Rhectomia Moure, Thectochlora Moure (Halictidae), and Bothranthidium Moure (Megachilidae) are recorded for the first time for Argentina. Whereas the genera Trichocerapis, Megalopta, Rhectomia, and Bothranthidium are cited for the first time in the country.